Atrial Natriuretic Peptide Promotes Neurite Outgrowth and Survival of Cochlear Spiral Ganglion Neurons in vitro Through NPR-A/cGMP/PKG Signaling - Sun, Fei; Zhou, Ke; Tian, Ke-yong; Zhang, Xin-yu; Liu, Wei; Wang, Jie; Zhong, Cui-ping; Qiu, Jian-hua; Zha, Ding-jun (Frontiers in Cell and Developmental Biology, 2021)
Sensorineural hearing loss (SNHL) is a dominant public health issue affecting millions of people around the globe, which is correlated with the irreversible deterioration of the hair cells and spiral ganglion neurons (SGNs) within the cochlea. Strategies using bioactive molecules that regulate neurite regeneration and neuronal survival to reestablish connections between auditory epithelium or implanted electrodes and SGNs neurites, would become attractive therapeutic candidates for SNHL. As an intracellular second messenger, cGMP can be synthesized through activation of particulate guanylate cyclase-coupled natriuretic peptide receptor by natriuretic peptides, which in turn modulates multiple aspects of neuronal functions including neuronal development and neuronal survival. As a cardiac-derived hormone, atrial natriuretic peptide (ANP) and its specific receptors (NPR-A and NPR-C) are broadly expressed in the nervous system where they might be involved in the maintenance of diverse neural functions. Despite former literatures and our reports indicated the existence of ANP and its receptors within the inner ear, particularly in the spiral ganglion, their potential regulatory mechanisms underlying functional properties of auditory neurons are still incompletely understood. Our recently published investigation revealed that ANP could promote the neurite outgrowth of SGNs by activating NPR-A/cGMP/PKG cascade in a dose-dependent manner. In the present research, the influence of ANP and its receptors-mediated downstream signaling pathways on neurite outgrowth, neurite attraction and neuronal survival of SGNs in vitro were evaluated by employing cultures of organotypic explant and dissociated neuron from postnatal rats. Our data indicated that ANP could support and attract neurite outgrowth of SGNs, as well as possess a high capacity to improve neuronal survival of SGNs against glutamate-induced excitotoxicity by triggering NPR-A/cGMP/PKG pathway. The neuroregenerative and neuroprotective effects of ANP/NPRA/cGMP/PKG-dependent signaling on SGNs would represent an attractive therapeutic candidate for hearing impairment.